Electrophysiologic Confirmation of Heterogenous Motor Polyneuropathy in Young Cats. (17th September 2014) - Aleman, M.; Dickinson, P.J.; Williams, D.C.; Sturges, B.K.; LeCouteur, R.A.; Vernau, K.M.; Shelton, G.D.
<x xml:space="preserve">Abstract</x> Background Reports of motor polyneuropathies in young cats are scarce. Further, in‐depth electrophysiologic evaluation to confirm a motor polyneuropathy in young cats of various breeds other than 2 Bengal cats is lacking. Hypothesis/Objectives To confirm a motor polyneuropathy in young cats of various breeds. Animals Five young cats with heterogenous chronic or relapsing episodes of weakness. Methods Retrospective case series. Cats were presented for evaluation of generalized neuromuscular disease and underwent electrophysiologic examination including electromyography, nerve conduction, and repetitive nerve stimulation. Minimum database and muscle and nerve biopsy analyses were carried out. Descriptive statistics were performed. Results Disease onset was at 3 months to 1 year of age and in 5 breeds. The most common clinical sign (5 of 5 cats) was weakness. Additional neurologic deficits consisted of palmigrade and plantigrade posture (4/4), low carriage of the head and tail (4/4), and variable segmental reflex deficits (5/5). Motor nerve conduction studies were abnormal for the ulnar (4/4), peroneal (5/5), and tibial (2/2) nerves (increased latencies, reduced amplitudes, slow velocities). A marked decrement was observed on repetitive nerve stimulation of the peroneal nerve in 3 cats for which autoimmune myasthenia gravis was ruled out. All sensory nerve conduction studies were normal. Histologic evaluation of muscle and nerve biopsies supported heterogenous alterations consistent with motor polyneuropathy with distal nerve fiber loss. Conclusions and Clinical Importance Heterogenous motor polyneuropathies should be considered in young cats of any breed and sex that are presented with relapsing or progressive generalized neuromuscular disease.